Garden-path sentences and the diversity of their (mis)representations - Ceháková, Markéta; Chromý, Jan (PloS one, 2023)
Previous studies have reliably shown that the initial misanalysis of garden-path sentences lingers even after the whole sentence is processed. However, other aspects of the resulting representation of these sentences are far from being clear. Some authors argue that comprehenders form a full analysis of the sentence which is faithful to the input and that the fact that the misanalysis lingers is due to an inhibition failure. Recently, it has been shown that comprehenders might not manage to create a coherent representation at all, at least in the case of more demanding garden-path structures. The aim of the current paper is to examine resulting representations of garden-path sentences in more detail. To do this, four self-paced reading experiments in Czech were conducted, which differed in the presentation mode (word-by-word and sentence-at-once) and comprehension question format (yes-no questions and open-ended questions). The experiments replicated effects typical for the lingering initial misanalysis, but provided mixed evidence for other aspects of resulting representations. In most cases, participants managed to build a coherent representation that was faithful to the input. However, both the quantitative and qualitative analysis of the results showed that comprehenders sometimes maintained multiple local interpretations at once or even failed to build a coherent representation of a garden-path sentence. Thus, we argue that resulting representations of garden-path sentences are in fact not uniform, but rather diverse, and they vary both in their faithfulness to the presented input and in their internal coherence.
Keywords: Language; Comprehension; Semantics; lidé; Inhibition, Psychological; pochopení; čtení; Reading; jazyk (prostředek komunikace); sémantika; inhibice (psychologie); Humans